1998
DOI: 10.1046/j.1365-2222.1998.00217.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum eosinophil cationic protein as a marker of eosinophilic inflammation in asthma

Abstract: The data suggest that serum ECP level reflects the intensity of eosinophilic airway inflammation, as well as the disease activity, and may be useful as an inflammatory marker in asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
53
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 27 publications
8
53
1
1
Order By: Relevance
“…The serum level of ECP is known to be a marker of activated eosinophils in patients with bronchial asthma (Venge et al 1999). Increased serum ECP levels in asthma patients in the present study are consistent with the levels in a previous report in symptomatic asthma patients (Niimi et al 1998).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The serum level of ECP is known to be a marker of activated eosinophils in patients with bronchial asthma (Venge et al 1999). Increased serum ECP levels in asthma patients in the present study are consistent with the levels in a previous report in symptomatic asthma patients (Niimi et al 1998).…”
Section: Discussionsupporting
confidence: 82%
“…The levels of these factors at the exacerbations caused by URTIs did not differ from those in patients with acute asthma without obvious URTIs. The levels of these factors are consistent with the data as previously described in acute asthma without obvious URTIs (Montefort et al 1994;Yokoyama et al 1995; Niimi et al 1998). These findings, therefore, suggest that virus infection may also produce the factors that induce inflammation and bronchospasm observed in acute asthma caused by other than virus infection.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A previous study has suggested that serum ECP reflects the degree of eosinophilic inflammation in the airways and the disease activity in asthma [21]. Three studies examining the correlations between serum and sputum ECP levels showed contrasting results, since CLAMAN et al [22] found a positive correlation, whereas VIRCHOW et al [23], and, more recently, PIZZICHINI et al [24] failed to find such correlations.…”
Section: Discussionmentioning
confidence: 68%
“…Due to its ability to reducing the number of mast cells and eosinophil, weakening eosinophilic activation, and lowering hyper-responsiveness of airways, glucocorticoids have been widely administered as primary drugs for treating chronic and acute BA (Barnes 2011). Serum ECP is a low molecular weight cationic basic protein and is secreted by activated eosinophils that can be functioned as a reference parameter for the evaluation of asthma severity (Niimi et al 1998). In this study, we explored the diagnostic efficiency of serum ECP on the efficacy of ICS therapy in children with BA with the underlying incentive to provide a better clinical evaluation for asthma severity.…”
Section: Discussionmentioning
confidence: 99%